Constraints and Perspectives for Sustainable Wheat Production in Tajikistan - Husenov, Bahromiddin; Otambekova, Munira; Muminjanov, Hafiz; Morgounov, Alexey; Asaad, Siham; Garkava-Gustavsson, Larisa; Johansson, Eva (Frontiers in Sustainable Food Systems, 2020)
Wheat is a major crop with a key role for food security in Tajikistan, contributing 60% of daily calorie intake for the Tajik population. A clear understanding of the major constraints and opportunities relating to wheat production and sustainability in farmers' fields is therefore required. A survey of 210 different wheat fields of different sizes, located in different agricultural zones in Tajikistan and at different altitudes, was conducted during three consecutive years (2012–2014). A questionnaire on wheat production and sustainability, seeking overall information about farms and specific data on crop management practices, was applied. It was accompanied by surveillance of field status concerning diseases, pests, weeds, and influence of abiotic stresses. In addition, a screening was carried out on major Tajik wheat varieties and advanced breeding lines, to assess their resistance to important diseases. The results showed that the agronomic knowledge of Tajik farmers was generally poor and that wheat yield was low, affecting social, economic, and environmental sustainability. The farms surveyed were generally small, growing winter wheat for human consumption year after year. Seeds were hand-broadcast at the optimal sowing time, without chemical treatments and either wheat or technical crops were used as preceding crops. Most farmers used nitrogen fertilizer and irrigation but no weed treatment. The low knowledge status of wheat farmers influenced crop performance and were correlated with lack of crop rotation, while the lack of pest management resulted in high levels of weeds and severe insect damage. While some similarities were shared by most wheat fields surveyed, there was also some variation in wheat crop performance among farms in relation to their size, year of study, agricultural zone, and altitude. Wheat production on small farms still relied heavily on manual labor, while larger farms used more machinery. However, larger farms were not more successful wheat producers than small farms. Most of the Tajik wheat varieties and lines screened were found to be susceptible to at least one of the diseases screened for, i.e., stripe rust, leaf rust, and common bunt. Our findings demonstrate a need for concerted action to overcome wheat yield constraints and achieve sustainability in crop production in Tajikistan. Education of farmers appears key to improving social, economic, and environmental sustainability. Use of certified seed of suitable wheat varieties and appropriate crop management practices, including weed control while also taking biodiversity into consideration, are other important measures for increasing wheat yield and improving sustainability.